C-15 ACETOGENINS FROM THE MARINE ALGA Chondria - Antonius R.B. Ola; Bruce F. Bowden (Universitas Gadjah Mada, 2008)
(-) Z-Pinnatifidenyne, a novel C-15 acetogenin has been isolated along with the known compound (+)-3Z,6R,7R-obtusenyne and (+) (3Z)-laurenyne from the Australian red alga Chondria armata. The structures of the compounds were elucidated based on spectral data analysis including 2D NMR spectroscopic experiment.